The Prisoner - Sudry, Asaf (Cinema Project, 2009)
Verzio FF Submission Released after years in prison, a sixty-year-old man must come to grips with the fact that his family has abandoned him. Forced to face his freedom alone, he discovers one day that he has a daughter. She is his one chance to make up for his past and achieve his final redemption. A film about the difficulties faced by longtime prisoners adjusting to a new yet utterly different world of freedom.